FKBP8, a new member of the PIK3C3/VPS34 complex - Aguilera, Milton Osmar (2022)
Macroautophagy/autophagy is an adaptable pathway involved in the degrada- tion of very different targets that include proteins, organelles, or even invading intracellular microorganisms. The regulation of this complex pathway depends on a great number of proteins, some common for the majority of the processes and others specific for a particular autophagic event. Nevertheless, the kind of interaction between the players contributes to determining the specificity of the regulation. In a recent study, we found a new regulatory protein of starva- tion-activated autophagy called FKBP8. The absence of this protein impairs autophagy activation produced by serum starvation and its overexpression can activate the pathway in cells incubated in full media. Besides, we found that the FKBP8 function is mediated by the interaction with the PIK3C3/VPS34- containing complex. Previously, FKBP8 has been shown to participate in mito- phagy. In the latter process, FKBP8 works inducing mitochondrial fission, and also it functions as a receptor protein through its LIR domain to direct autop- hagy. In contrast to mitophagy, in starvation-activated autophagy, not the LIR but the transmembrane domain of FKBP8 is necessary for the regulatory func- tion and interaction with the PIK3C3 complex.